Pasteurella multocida Infection in a neonate: evidence for a human-to-human horizontal transmission. - Tania Siahanidou; Gika, Georgia; Skiathitou, Anna-Venetia; Oikonomopoulos, Theodoros; Alexandrou-Athanassoulis, Helen; Koutouzis, Emmanouil I; Syriopoulou, Vassiliki P (Pediatr Infect Dis J, 2012)
Pasteurella multocida is usually transmitted by animal contact; however, in a significant proportion of cases, no animal exposure can be identified. Although vertical transmission has been identified in neonates, horizontal human-to-human spread has not been documented. A case of neonatal sepsis and meningitis resulting from horizontal transmission of P. multocida is described.
Keywords: Bacterial; disease transmission; Female; Humans; Infant; Infectious; Meningitis; Newborn; Pasteurella Infections; Pasteurella multocida; Sepsis